Cutaneous allodynia and thermal thresholds in chronic migraine: The effect of onabotulinumtoxinA - Ozarslan, Melek; MATUR, ZELİHA; MATUR, ZELİHA; Tuzun, Erdem; Oge, Ali Emre (My University, 2022)
Objective: Cutaneous allodynia (CA) is a common symptom in migraine. Its incidence is more frequent in the chronic migraine (CM). CA usually occurs during pain attacks. However, it can also be interictal and its frequency and severity seem to be correlated with the duration of the disease. Several quantitative sensory testing (QST) studies have revealed variable results about mechanical and thermal allodynia accompanying migraine. This study aimed to investigate the effects of CA and onabotulinumtoxinA (BoNT-A) injection on the thermal thresholds measured by QST in patients with CM. The effects of BoNT-A on headaches, CA, and other accompanying symptoms of migraine were also evaluated. Methods: Single BoNT-A injections were performed in 22 female cases (mean age: 38.1 +/- 7.2 years) with CM. Patients were evaluated at 1-7 days before, 28-35, and 84-91 days after the injection. The 22 healthy women in the control group (mean age: 36.6 +/- 7.6 years) were examined once. Headache and its characteristics, medication intake, allodynia, presence of anxiety, and depression symptoms were evaluated through relevant scales. The heat (HDT) and cold (CDT) detection thresholds on the forehead and hand were measured bilaterally with QST. The presence of brush allodynia for patients was examined by applying a 4 x 4 gauze pad over the same areas.Results: The patients in the CM group had migraine for an average of 22.5 +/- 6.1 years and CM for 6.1 +/- 3.2 years. The average number of painful days per month was 22.1 +/- 4.0 days. All the patients had migraine attacks with CA (mean 5.6/month). The average allodynia symptom checklist (ASC-12) score was 7.8 +/- 6.2. Thermal thresholds measured in the patients with CM were similar to those of the controls. Thermal thresholds did not show significant differences between the symptomatic and the asymptomatic sides at the last migraine attack. There was also no correlation between the allodynia revealed by the physical examination and the thermal thresholds detected by QST. The ASC-12 score decreased significantly with BoNT-A injection (p = 0.030), but no significant change was observed in thermal thresholds after this treatment. Conclusion: There was no significant correlation between CA and thermal thresholds. BoNT-A was successful in relieving headache and other associated symptoms, including CA, but had no significant effect on QST parameters.